CD2AP regulates SUMOylation of CIN85 in podocytes - Tossidou, Irini; Niedenthal, Rainer; Klaus, Malte; Teng, Beina; Worthmann, Kirstin; King, Benjamin L.; Peterson, Kevin J.; Haller, Hermann; Schiffer, Mario (Molecular and Cellular Biology, 2012)
Podocytes are highly differentiated and polarized epithelial cells located on the visceral side of the glomerulus. They form an indispensable component of the glomerular filter, the slit diaphragm, formed by several transmembrane proteins and adaptor molecules. Disruption of the slit diaphragm can lead to massive proteinuria and nephrotic syndrome in mice and humans. CD2AP is an adaptor protein that is important for the maintenance of the slit diaphragm. Together with its paralogue, CIN85, CD2AP belongs to a family of adaptor proteins that are primarily described as being involved in endocytosis and downregulation of receptor tyrosine kinase activity. We have shown that full-length CIN85 is upregulated in podocytes in the absence of CD2AP, whereas in wild-type cells, full-length CIN85 is not detectable. In this study, we show that full-length CIN85 is postranslationally modified by SUMOylation in wild-type podocytes. We can demonstrate that CIN85 is SUMOylated by SUMO-1, -2, and -3 and that SUMOylation is enhanced in the presence of CD2AP. Conversion of lysine 598 to arginine completely abolishes SUMOylation and leads to increased binding of CIN85 to nephrin. Our results indicate a novel role for CD2AP in regulating posttranslational modification of CIN85. © 2012, American Society for Microbiology.
CRIS-Team Scopus Importer:2020-11-12